Prinsip Tata Kelola Perusahaan Yang Baik dan Prinsip Kewajaran Sebagai Batasan Vicarious Liability Perseroan Terbatas - Saputri, Theodora Pritadianing (Refleksi Hukum: Jurnal Ilmu Hukum, 2024)
A limited liability company, as a fictional person in law, is represented by its organs in carrying out legal actions. When a third party suffers damages, the limited liability company should be responsible for the actions of its representative. The question arises whether the limited liability company should remain responsible for the action of its representative which is beyond its authority (ultra vires). This study uses a normative juridical research method to set limits for the application of vicarious liability against a limited liability company. This article draws several limitations which are (1) the link between the unlawful act and the perpetrator's position as a limited liability company employee, (2) the fact that the limited liability company through its management has implemented good corporate governance including carrying out internal controls, and (3) victims, relying on reasonableness principle, are allowed to assume that employees are carrying out their scope of work.